Evaluation the possibility of the occurrence of progressive collapse in steel moment frames (ordinary, intermediate and special) due to sudden column removal - Kourosh Mehdizadeh (Iranian Society of Structrual Engineering (ISSE), 2018)
Buildings during their useful life may be affected by different external threats. These threats can harm the key elements of buildings and thus lead to progressive collapse. In recent decades, researchers have been working extensively on how to deal with abnormal events such as explosions, accidents and terrorist attacks. In this study, a typically 5-story steel structure with ordinary, intermediate and special (low, medium and high ductility levels) moment frames designed based on internal regulations and all criteria have been controlled. Then by selecting a middle two-dimensional frame, the possibility of occurrence of progressive collapse caused by the sudden removal of corner and middle columns of all three frames have been investigated based on the guidelines of the GSA and the UFC. By defining the concentrated plastic hinges at the element ends and by using the strength and stiffness attenuation parameters resulted from laboratory studies of other researchers, non-linear dynamic behavior of frames due to sudden removal of columns have been investigated. Results show that the possibility of damage to special moment frame is more than the intermediate and ordinary moment frames. Also the results indicate unlike the seismic retrofitting that providing ductility is an important method to reduce damages to the buildings, for damages caused by gravity loads, higher strength and stiffness can limit the progress of damages.